Sistem Informasi Inventory Berbasis Website (Studi Kasus : Pada Toko Obyth) - Thalia, Kristin Mamit; Oktaviyani, Enny Dwi; Sylviana, Felicia (Universitas Palangka Raya, 2021)
Inventory data on Obyth Store is still made in the big agenda book, so store owners and cashiers have difficulty when viewing the inventory data information of existing goods. Therefore, it takes a system of information on inventory of goods using the Reorder point method. This method helps the shop owner to check the inventory quantity of goods without having to go around first, and avoid running out of stock the amount of inventory and the store owner can know the point of time when to rebook. This system uses 2 methods namely waterfall as a software development method and Re Order Point method as a method in the inventory information system created. Re order point has 3 factors to get the result of its re order point, namely lead time, average usage, and safety stock. Based on the waterfall method stage there are several stages namely requirement definition, system and software design, implemetation and unit testing, integration and system testing and operation. The software used in building this website is Sublime, MySQL, and XAMPP